Les Ambassadeurs de Henry James : de la rhétorique à la sémiotique - Marie-Odile Salati (Caliban: French Journal of English Studies)
This article focuses on the diplomatic use of language in Henry James’s late novel The Ambassadors, where the American family envoy attempts to entice the son and heir back home, away from his refined social circle and a life of pleasure in Paris. However the venture fails to meet the requirements traditionally expected of an ambassador’s mission. The protagonist soon finds to his dismay that his interlocutors are not playing the game according to the rules, that his straightforward speech is defeated by their ambiguous replies and that their duplicity precludes his using the rhetorical art of persuasion. Taking his cue from their behaviour, he switches from speech to reserve and observation, becoming alert to non-verbal signs likely to assist him in his quest for meaning. The goal of our analysis is ultimately to investigate the way in which the theme of diplomacy serves the novelist’s representational purposes and to identify the meeting-points of the two arts.